A comparison of proton, antiproton and meson distributions in final states of deep inelastic muon scattering - Aubert, J; Bassompierre, G; Becks, K; Benchouk, C; Best, C; Böhm, E; de Bouard, X; Brasse, F; Broll, C; Brown, S; Carr, J; Clifft, R; et al. (1984)
New results on the forward produced protons and antiprotons in high energy muon-nucleon scattering are presented. Their W2, z and p2T dependences are compared with those of the other charged hadrons. Significant differences are observed which can be related to the flavour content of the target and to a difference between the baryon content of quark and gluon jets. © 1984.